Lip Symmetry Evaluation Of The Gentur's Method Compared To Fisher Techniques For Unilateral Cleft Lip Repair - Kreshanti, Prasetyanugraheni; Kiat, Muhammad Irsyad (Lingkar Studi Bedah Plastik Foundation, 2017)
Background : Cleft lip and palate are the most common congenital anomalies that were found in plastic surgery. There are so many techniques for unilateral cleft lip repair. Rotation-advancement method by Gentur based on Millard technique has become the most widely used in unilateral cleft lip repair in RSCM. The Fisher technique repair is a modified technique based on approximation of anatomical subunit of the lip. The purpose of this study is to objectively compare and evaluate the lip symmetry of these two techniques. Method : Two senior board-certified plastic surgeons will perform different surgical techniques for the unilateral cleft lip: rotation-advancement technique by Gentur and Fisher technique. This study prospectively analyzed preoperative and postoperative of randomized single blinded patients who underwent unilateral cleft lip repair performed by each surgeon in 2016. Using caliper, facial points on the cleft and non-cleft sides were measured, including height and symmetry of Cupid’s bow, width and height of the nasal vestibule, height of the vermilion, and alar base position. Ratios of cleft side to non cleft side measurements were calculated to standardize comparisons between patients. Result : From July-October 2016, 14 patients performed surgery as preliminary data, showed that there are statistically difference in length of design and surgery time. Preoperative, comparable of cupid’s bow and vermillion showed statistically difference. Although, we found no statistically difference in postoperative ratio. Conclusion : Lip symmetry outcomes after cheiloplasty procedure are same between Gentur method and Fisher technique.